Mutation of yeast PEX6 gene inhibits glycolysis and mitochondrial respiratory chain but promotes glycogen and trehalose biosynthesis and necrosis - Bui, Van Ngoc; Chu, Hoang Ha (Academia Journal of Biology, 2025)
In yeast, Pex6 (peroxisomal biogenesis factor 6) encoded by the PEX6 gene plays a crucial role in peroxisomal protein import, cell viability, and necrosis. Moreover, the activity of some key glycolytic enzymes is changed due to DNA damage or oxidative stress, leading to the diversion of metabolic flux into other biochemical pathways, such as the pentose phosphate pathway (ppp), hexosamine biosynthesis pathway (HBP), and glycogen and trehalose synthesis. Thus, the present study aims to examine the role of the PEX6 gene by using the BY4741 (wild type) and specific knock-out yeast strains (∆pex6). The activity of this gene in these biochemical pathways in response to DNA damage triggered by methyl methanesulfonate (MMS) treatment would be elucidated by using enzymatic, Gloxo, and OxoPlate® assays, flow cytometry, and chromatography. The findings obtained show that DNA damage significantly inhibited the activity of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and pyruvate kinase (PYK), mitochondrial respiration, cell growth, and ATP synthesis. However, DNA damage intensively promotes the activity of glucose-6-phosphate dehydrogenase (G6PDH) and the synthesis of uridine-diphosphoglucose-N-acetylglucosamine (UDP-NacGlu). Subsequently, the glucose flux was not diverted to the TCA cycle due to prohibited mitochondrial activity and oxygen consumption, but to the ppp as a result of increased G6PDH activity and to glycogen/trehalose accumulation because of enhanced UDP-NacGlu levels. The cells, especially the mutant ∆pex6, utilize glycogen/trehalose as major energy reserves to maintain their energy and survival, and induce necrosis as a cellular defense mechanism in response to DNA damage. These results suggest that a fully functional PEX6 plays a major role in cell proliferation, energy metabolism, and the cellular defense mechanism in response to DNA damage.